Desempenho dos imunomarcadores MCM2, bcl2 e Vilina no diagnóstico diferencial de adenocarcinomas endocervicais e endometriais - Cysneiros, Maria Auxiliadora de Paula Carneiro (2013)
Endocervical and Endometrial Adenocarcinomas are uterine neoplasms with different biological behaviors and different treatments, being all the therapeutic plan based on the origin site of these tumors. To differentiate these two neoplasms, many times the immunohistochemical study is used as an ancillary tool to assist and complement histopathological examination. Previous studies have investigated the value of various markers in the distinction of these neoplasms, with results varying and sometimes conflicting. In this study the impact of the MCM2, bcl2 and villin markers in the differential diagnosis of endocervical and endometrial adenocarcinomas, associated or not to a traditional markers panel formed by CEA, vimentin, RE, RP and p16, was evaluated. Material and methods: A tissue microarray (TMA) was constructed using paraffin-embedded, formalin-fixed tissues from 104 hysterectomy specimens and conizations. Out of the 104, 51 samples were represented by unequivocal cases of adenocarcinomas of the endocervice and 53 represented unequivocal cases of endometrial adenocarcinomas. The sections of tissue microarray block were immunostained with the eight antibodies in study and to the antigen-antibody reaction preview it was used the polymer detection system. Scoring of immunostaining was interpreted using the German semi quantitative scoring system in considering the staining intensity and area extent of marker expression. The final Immunoreactive score was determined by multiplying the positive intensity and the positive area extent scores. The threshold for differentiating between final positive and negative immunostaining was set at 4 for interpretation (0-3 = negative; 4-12 = positive). Results: The univariate analysis showed that out of the eight markers, seven (CEA, vimentin, RE, RP, p16, MCM2 and bcl2) showed good performance in the distinction between the endocervical and endometrial origin. The multivariate analysis showed that CEA, p16 and MCM2 were the strongest predictors of site of origin. In the evaluation of six panels built by various combinations of immunomarkers , the panel with the lowest accuracy was that represented by MCM2, bcl2 and villin. The villin did not show any statistically significant difference in the differential diagnosis of these adenocarcinomas. Despite the MCM2 and bcl2 have revealed significant differences of frequency between the two sites of origin, they did not demonstrate additional benefit when added to a traditional panel. Conclusion: According to our study, the inclusion of MCM2, bcl2 and villin in the immunohistochemical assessment of uterine adenocarcinomas, added no supplementary value in the differentiation of these two neoplasms.